Análisis tributario de la economía naranja en la era digital en la ciudad de Tunja periodo 2018 a 2020. (2021)
Colombian legislation wants to implement an innovation strategy in the digital economy so that companies can innovate in such a way that they can venture into digital businesses, as this has been seen in countries like Mexico and Peru. In Colombia, this is being seen in the BEPS (Periodic Economic Benefits) programs, becoming a savings alternative that allows retirement for people whose income is less than the current legal monthly minimum wage, the Xaverian university seeks to give a sense of life to medium and small companies based on competitiveness using technological tools that are available to all consumers using digital commerce by electronic means. These can also benefit from ICTs since they are found in 58 more countries, for this reason the digital economy can give innovation and growth to companies in Colombia. Good management of the orange economy in companies can guarantee permanence in the market not only nationally but also internationally, safeguarding the intellectual property rights of each enterprise, this being very important to the public finances of the nation and of each of the municipalities where the industrial, commercial, financial or service activity is carried out, in this case we want to analyze the orange economy in the municipality of Tunja.